2016
DOI: 10.1002/app.44521
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of polyurethane/silica aerogel nanocomposite materials

Abstract: In this investigation, silica aerogel (SA)/Rigid Polyurethane (PUR) foam composites and silica aerogel/Polyurethane (PU) composites were prepared by dry mixing of granular and grinded silica aerogels with polyol part. They were then combined with diisocyanate part. Three different types of PUR foams and an elastomeric coating grade of PU were studied as well. Results show that thermal conductivity of foams did not decrease by adding silica aerogel. It even increased for some grades which is assumed to be due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 52 publications
0
19
0
1
Order By: Relevance
“…Since aerogels were first investigated as low sound speed materials, more and more studies about sound the absorption of aerogels were reported, most of which were related to soft organic fiber-composite SiO 2 aerogels [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ], such as silica–cellulose hybrid aerogels, polyurethane/silica aerogels, polyethylene terephthalate fiber nonwovens/silica aerogels, unplastisized polyvinyl chloride/silica aerogels and so on. All of these aerogel composites possess high flexibility and porosity, which inspired us to test the sound absorption of the resultant MSQ aerogels with similar properties.…”
Section: Resultsmentioning
confidence: 99%
“…Since aerogels were first investigated as low sound speed materials, more and more studies about sound the absorption of aerogels were reported, most of which were related to soft organic fiber-composite SiO 2 aerogels [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ], such as silica–cellulose hybrid aerogels, polyurethane/silica aerogels, polyethylene terephthalate fiber nonwovens/silica aerogels, unplastisized polyvinyl chloride/silica aerogels and so on. All of these aerogel composites possess high flexibility and porosity, which inspired us to test the sound absorption of the resultant MSQ aerogels with similar properties.…”
Section: Resultsmentioning
confidence: 99%
“…Gözenekli yapıda üretilen silika, ısı yalıtım uygulamalarında oldukça fazla dikkat çekmiştir. Bu tür maddelerin üretiminde sodyum silikat, tetraetoksi silan (TEOS), tetrametoksi silan metiltrimetoksisilan, 3 amino-propil trietoksi silan prekürsor olarak kullanılmaktadır [7]. Ancak silika aerojel üretimi sentezlenme süresi ve maliyeti yüksek olan bir süreçtir.…”
Section: Introductionunclassified
“…used a perforation process to provide rigid polyurethane (PU) foam plates with greater load absorption and better acoustic absorption at medium and high frequencies. Dourbash et al . proposed silica aerogel/rigid polyurethane foam composites and silica aerogel/polyurethane composites.…”
Section: Introductionmentioning
confidence: 99%
“…In order to attain acoustic absorption, Lin et al 3 used a perforation process to provide rigid polyurethane (PU) foam plates with greater load absorption and better acoustic absorption at medium and high frequencies. Dourbash et al 4 proposed silica aerogel/rigid polyurethane foam composites and silica aerogel/polyurethane composites. They found that adding silica aerogel to elastomeric PU led to improved acoustic insulation performance.…”
Section: Introductionmentioning
confidence: 99%